Understanding the influence of abortion on 2024 US elections - Kass, Dara; Choo, Esther K; Rodriguez, Maria I (BMJ. British medical journal (Clinical research ed.), 2025)
Dara Kass and colleagues consider why, despite predictions to the contrary, abortion was not a major driver of votes during the presidential election and what it means for future advocacy